Pre and post-fire situation, of an ecosystem of the Roble-Hualo forest type, Maule region, Chile - Rosales-Rodríguez, Jorge Alejandro (2018)
Forest fires are one of the major causes of ecosystem degradation in Chile. The 2016-2017 forest fire season was notable for the affected area, including a forest and scrub, of the Roble-Hualo forest type, of high conservation value. Therefore, this study aimed to evaluate the effect of the fire in both formations, on the structure of the canopy through the use of hemispheric photographs. In addition, the effect of the fire on chemical variables of soil, diversity and abundance of vegetation were quantified. The results indicated a clear degradation of the structure of the canopy of the forest and scrub, increase in the potential radiation on the forest floor, reduction of the foliar area and coverage of the canopies on the ground. Also, some chemical variables such as pH, organic matter (MO%), sum of bases (Sb) and available potassium (Kd) increased in the scrub soil, but not in the forest floor. Post-fire regeneration was scarce in both coverages, in addition there was a considerable loss of arboreal and shrubby diversity, thus affecting the composition of the vegetation, in the forest and in the scrub.